Determination of fiber length and juvenile and mature wood zones from Hevea brasiliensis trees grown in Brazil - Ferreira, A. L. [UNESP]; Severo, Elias Taylor Durgante [UNESP]; Calonego, Fred Willians [UNESP] (Springer, 2011)
The aim of this study was to verify the average fiber length and the juvenile and mature wood zones from Hevea brasiliensis proveniences from a reforestation area in São Paulo, Brazil. For this purpose, five Hevea brasiliensis trees were randomly collected from a 50-year-old plantation, located in Balsamo, São Paulo, Brazil. The trees were cut and five flat sawn boards were obtained. The juvenile and mature wood zones were determined by fiber length measurement from the pith to the bark. The results showed that: (a) the juvenile wood of this species occurred approx. between 40 and 55 mm, from the pith, and from this point forward, the mature wood zone was found; (b) there was a significant difference between the average fiber length of juvenile wood (1.26 mm) and mature wood (1.51 mm).